9=r+7-6

Simple and best practice solution for 9=r+7-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9=r+7-6 equation:


Simplifying
9 = r + 7 + -6

Reorder the terms:
9 = 7 + -6 + r

Combine like terms: 7 + -6 = 1
9 = 1 + r

Solving
9 = 1 + r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-1r' to each side of the equation.
9 + -1r = 1 + r + -1r

Combine like terms: r + -1r = 0
9 + -1r = 1 + 0
9 + -1r = 1

Add '-9' to each side of the equation.
9 + -9 + -1r = 1 + -9

Combine like terms: 9 + -9 = 0
0 + -1r = 1 + -9
-1r = 1 + -9

Combine like terms: 1 + -9 = -8
-1r = -8

Divide each side by '-1'.
r = 8

Simplifying
r = 8

See similar equations:

| 8-2(a-6)=-4-3(a+5) | | -22=-7y+4(y+2) | | x^2-8x-32=-32 | | -2[3x+3(K-8)]=-2[3(x+7)] | | -300y=400 | | 8-2(a-6)=-4-3a(a+5) | | A(X-C)=B(X-C) | | x+x+20=30+x+100 | | 8r+2r=-8r | | y=3/4(3/4)-6 | | O=x^2-4x | | -3x+6(12-5x)=6 | | -4(3+x)+4(x-6)=-4 | | k^2-6k-9=18 | | -4x+7x-7=3(x-6)-1 | | 22+3x=2(x+3) | | -2y=-24+10x | | 25-7=18 | | 6-2(4x+1)=5x-2(2x+7) | | -5.2=m-6.8 | | -(x+7)=36 | | 5y+50-8= | | 19.6+n=24.62 | | -20=f/2 | | 2t^2-30t+0=0 | | X/-9=-14 | | 17=-6-6x-1 | | -10x-2(12-5x)=-24 | | abs(3x-5)=abs(4x-2) | | 8-(x*x+7)=-35 | | .22(x+6)=.2x+5.3 | | x/3-9/4=x/6-1/2 |

Equations solver categories